Parental engagement in School: Perspectives of Arabic speaking Parents of English language learners (ELLs) and Primary School Teachers. - Srabiet, Souaad (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2025)
Parents' engagement in the education of their children tend to have a positive impact for their academic, behavioural, social and emotional development regardless of their ages, socioeconomic, racial, ethnic and linguistic backgrounds. Parental engagement may have potential additional benefits for parents, teachers and schools as well. However, the levels of family-school engagement in culturally and linguistically diverse educational contexts might be complicated as immigrant parents might not be actively engaged due to many, immigration related, challenges (Turney & Kao, 2009; Kim, 2009; Koyama & Bakuza, 2017; Antony-Newman, 2019). As Ireland is becoming an increasingly diverse country, because of large-scale inward migration, the number of children in Irish schools for whom English is not the language spoken at home, referred to as English language learners (ELLs), is increasing creating challenges to the education system. Those challenges might include achievement gap between ELLs and their Irish counterparts as well as a diversity gap between homogenous white Irish teachers and the linguistically and culturally diverse pupils and their families. The way immigrant parents of ELLs are engaging with their children's education and schooling, in Irish schools, is lacking and needed close investigation. The aim of this research is to investigate the extent to which immigrant parents of ELLs and Irish primary school teachers work together to support ELLs in the context of four Irish primary schools in Dublin. Perceptions, experiences, patterns of engagement and challenges faced by parents and teachers were investigated. A mixed methods approach was taken combining quantitative and qualitative methods to develop understanding of multiple perspectives of both group participants. Teachers perceptions were assessed using an online, anonymous survey containing quantitative and qualitative questions. Parents perspectives were examined through individual semi-structured interviews, using both Arabic and English languages, as main source of data followed by focus group discussions in Arabic language to enrich data from the individual interviews. Descriptive statistics and thematic analysis were used to analyse the quantitative and qualitative data gathered. Findings indicate that despite most teachers and parents' positive attitudes towards family-school engagement, the overall levels of parental engagement in most of the participating schools were limited and constrained by challenges resulting from many factors, some related to families and others related to schools. The most evident challenges were due to linguistic and cultural differences between Arabic-speaking immigrant families and Irish schools causing many differing views and attitudes among parents of ELLs and teachers of how parental engagement should be. While parents of ELLs were perceived by teachers as not enough engaged in their children's education, lacking the knowledge about the importance of their childrens education, Arabic-speaking parents of ELLs, however, showed having awareness towards their roles in children's learning and development demonstrating many positive engagement practices at home that appeared to be impacted by their linguistic, cultural and religious values. To develop effective ELL parental engagement, Irish schools need to embrace culturally and linguistically responsive educational and parental engagement opportunities and to develop welcoming, equitable schools that represent the cultural backgrounds of the pupils, and their families.
APPROVED
Keywords: Parental Enagagement of Arabic-speaking immigrant parents in Irish Primary schools; ELL Parental Engagement Arabic-speaking parents